Removal of entrapped rings from swollen fingers by a nondestructive technique - Echem, Richard C.; Eyimina, Phillip D.; Adiela, Vincent V. U. (International Journal of Research in Medical Sciences, 2019)
Background: Ring entrapment is uncommon in our environment. It is necessary to remove entrapped rings and the removal techniques could be either destructive or non-destructive. The aim of this study is to present a non-destructive method of entrapped ring removal. Methods: A prospective study of patients who presented to the University of Port Harcourt Teaching Hospital, Port Harcourt between 1st October 2007 and 30th September 2018, with entrapped finger ring(s). The authors developed a non-destructive technique of entrapped ring removal utilizing 1.5-2.5 mm electric cables. The cables are passed under the ring and looped over it. The surgeon and his first assistant applies traction towards the distal aspect of the finger through the cables while moving the cables from side to side around the finger, with the second assistant maintaining a counter-traction. Data obtained was analyzed using IBM’s Statistical Package for Social Sciences (SPSS) version 23. Results: During the period, there were 25 patients who had entrapped ring(s) in their fingers. Mean age was 22.92±9.33 years. There were 10 males and 15 females. Mean duration of ring entrapment was 5.72±4.57 days. Mean duration of ring removal was 63.6±46.58 seconds. Abrasion was the most common complication following initial removal attempts as well as this technique. The entrapped rings were all successfully removed. Conclusion: The electric cable technique is a simple, inexpensive and readily available method of entrapped ring removal.